Effect of essential oils on oral halitosis treatment: a review. (17th November 2020) - Dobler, Dorota; Runkel, Frank; Schmidts, Thomas
Abstract : Halitosis is a very common condition which may affect up to 30% of the population. In about 90% of the cases, halitosis originates in the mouth due to inadequate plaque control, periodontal disease, dry mouth, faulty restorations, and in particular due to excessive bacterial growth. Oral malodor is mainly caused by a microbial degradation of amino acids into volatile, bad‐smelling gases (volatile sulfur compounds – VSCs). Management of oral malodor is directed primarily at managing and reducing the VSC‐producing bacteria count as well as masking the odor. Essential oils have been used for this purpose in traditional medicine for centuries. In the present review, data on the antimicrobial activity of essential oils against relevant oral VSC‐producing bacteria are compiled and compared. Additionally, other positive aspects of essential oils with regard to oral odor are considered.